Adipose Tissue-Endothelial Cell Interactions in Obesity-Induced Endothelial Dysfunction - Li, Manna; Qian, Ming; Kyler, Kathy; Xu, Jian (Frontiers in Cardiovascular Medicine, 2021)
Obesity has a strong impact on the pathogenesis of cardiovascular disease, which raises enthusiasm to identify mechanisms linking excess adiposity to vascular injury. Adipose tissue has been recognized as an essential regulator of cardiovascular health, by mechanisms related to the secretion of bioactive products with a broad range of endocrine and paracrine effects on the vascular system. Endothelial dysfunction often precedes and leads to the development of cardiovascular diseases. Understanding interactions between adipose tissue and endothelial cells may help to identify mechanisms for obesity-induced cardiovascular disease. This Mini Review will discuss (1) the modes of the interactions as potential targets of endothelial dysfunction in obesity and (2) the related outstanding questions and future research directions.